2020
DOI: 10.1155/2020/8811516
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation Efficiency and Mechanism of Carbamazepine by Microbial Flocculant Extracted from Klebsiella pneumoniae J1

Abstract: The microbial flocculant (MFX) extracted from Klebsiella pneumoniae J1 was used to remove carbamazepine in prepared wastewater and domestic sewage. The influence factors and flocculation mechanism were studied. The optimal carbamazepine removal conditions for MFX were pH of 7-8, 7 mL of flocculant, 0.1 mL of coagulant, and 35°C, and the removal rate reached 81.75%. MFX was efficient in the removal of carbamazepine in both domestic sewage (75.03%) and secondary sedimentation tank effluent (69.76%). The pseudo-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nitrate nitrogen was more easily utilized by Klebsiella than ammonium nitrogen. The latest report on Klebsiella pneumoniae showed that the microbial flocculant produced by Klebsiella pneumoniae had an effective flocculation effect on carbamazepine production wastewater (Xing et al 2020). There are a few reports about Klebsiella strain PEER-REVIEWED ARTICLE bioresources.com Diao et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate nitrogen was more easily utilized by Klebsiella than ammonium nitrogen. The latest report on Klebsiella pneumoniae showed that the microbial flocculant produced by Klebsiella pneumoniae had an effective flocculation effect on carbamazepine production wastewater (Xing et al 2020). There are a few reports about Klebsiella strain PEER-REVIEWED ARTICLE bioresources.com Diao et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…J. Xing et al applied a microbial flocculant extracted from Klebsiella pneumoniae J1 to remove carbamazepine in wastewater and domestic sewage. This ecofriendly and highly efficient microbial flocculant is expected for practical applications in carbamazepine removal [18]. For nutrient recovery, X. Gu et al applied anaerobic baffled reactors for biohydrogen production out of molasses wastewater and analyzed hydrogen-producing acetogen's performance under increasing organic loads [19].…”
mentioning
confidence: 99%